Local organic: food rhetorics and community writing for impact - House, Veronica, author; Utah State University Press, publisher (Colorado State University. Libraries, 2025)
House explores the intersections between local food movements, sustainability, and civic engagement, emphasizing community connection's vital role in fostering food systems and describing how movements impact community health. The book blends academic rigor and practical insight.--Provided by publisher.
Introduction: Ecological Community Writing and the Power of Definitions -- On Lineage and Purpose: A Place to Begin -- Food Rhetorics and a Crisis of Definitions -- What's "Local" About Local Food? Rehinging Words to Meaning -- Crisis and Abundance Rhetorics in Moving People Toward Collaborative Engagement -- Writing Abundant Ecologies: From Theory to Collaborative Local Research -- Ecological Community Writing in an Abundant Foodshed with Constance Gordon -- Abundant Partnership: A Local, Organic Approach to Rhetoric and Writing Studies with Kerry Francis, Tim Francis, and Kelly Zepelin.
Keywords: Communication in ecology; Local foods -- Social aspects; Natural foods -- Social aspects